A Sustainable Regenerative Study for Borneo Tropical Aquapolis Architecture - Prayitno, Budi (2005)
The Borneo's local community and natural wisdoms provide various symbiotic techniques n?ared by water-based living culture in the past. However, it has been gradually abandoned due !many short-term visioned economic and political interests. This paper will present a regenerative study model that is aimed to maximize the use 0 of local resources of Borneo settlement in the form of daily available solar energy and water resources to built a highly sustainable design in tropical aquapolis architecture. Some sustainable technologies will be used here which are environmental friendly active strategies that are photovoltaics and the thermoelectricity and the others are passive strategies that are air ventilation, cooling and day lighting without excessive heat. This study will contribute Borneo to save a considerable amount of energy and water resources in the aquatecture and aquapolis context of Kalimantan river cities and to reduce polluted water gasses emission.